FORMATION OF MARKOWITZ PORTFOLIO INSURANCE USING SIMULATED ANNEALING WITH AND WITHOUT OPTION - ASTERLITA JANTORO, VIONY
The Simulated Annealing method, which is a random search method for solving optimization problems, uses an analog simulation of the annealing of solids, where the objective function to be minimized corresponds to temperature of the solid. This method allows the occasional acceptance of a new inferior solution in order to avoid being trapped in a local optimum. The lower the temperature, the smaller the chance of this new solution to be accepted. In this final project, this method is implemented on the well-known problem of portfolio selection, the Markowitz Mean-Variance Model. In this method, we look for the solution that minimizing the covariance which reflects the risk of the portfolio and then we determine the highest return with the lowest covariance can be made in the portfolio. In the portfolio formation, there is a strategy that can be used to protect the portfolio. The strategy is called portfolio insurance. The strategy maintains the portfolio value when the stocks price decrease, so that the risk of the portfolio can be minimized. The strategy is dividing investor’s fund into various investment such as stocks, bond, and options. By simulation, we can determine the best strategy in the portfolio formation.